Incidence, aetiology and prevention of musculoskeletal injuries in volleyball: A systematic review of the literature - Kilic, O.; Maas, M.; Verhagen, E.; Zwerver, J.; Gouttebarge, V. (European Journal of Sport Science, 2017)
Currently, there is no overview of the incidence and (volleyball-specific) risk factors of musculoskeletal injuries among volleyball players, nor any insight into the effect of preventive measures on the incidence of injuries in volleyball. This study aimed to review systematically the scientific evidence on the incidence, prevalence, aetiology and preventive measures of volleyball injuries. To this end, a highly sensitive search strategy was built based on two groups of keywords (and their synonyms). Two electronic databases were searched, namely Medline (biomedical literature) via Pubmed, and SPORTDiscus (sports and sports medicine literature) via EBSCOhost. The results showed that ankle, knee and shoulder injuries are the most common injuries sustained while playing volleyball. Results are presented separately for acute and overuse injuries, as well as for contact and non-contact injuries. Measures to prevent musculoskeletal injuries, anterior knee injuries and ankle injuries were identified in the scientific literature. These preventive measures were found to have a significant effect on decreasing the occurrence of volleyball injuries (for instance on ankle injuries with a reduction from 0.9 to 0.5 injuries per 1000 player hours). Our systematic review showed that musculoskeletal injuries are common among volleyball players, while effective preventive measures remain scarce. Further epidemiological studies should focus on other specific injuries besides knee and ankle injuries, and should also report their prevalence and not only the incidence. Additionally, high-quality studies on the aetiology and prevention of shoulder injuries are lacking and should be a focus of future studies.